Nanocellulose Film Properties Tunable by Controlling Degree of Fibrillation of TEMPO-Oxidized Cellulose - Wakabayashi, Moe; Fujisawa, Shuji; Saito, Tsuguyuki; Isogai, Akira (Frontiers in Chemistry, 2020)
A fibrous 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized wood cellulose/water slurry was disintegrated with a magnetic stirrer or high-pressure homogenizer under various conditions to prepare TEMPO-oxidized cellulose (TOC)/water dispersions with different degrees of fibrillation. The turbidity value of the as-prepared dispersion was used as a measure of the degree of nanofibrillation of the fibrous TOC slurry in water. The fibrillated TOC/water dispersions with low degrees of fibrillation had cellulose nanonetwork (CNNeW) structures consisting of both TOC nanofibrils (TOCNs) and unfibrillated TOC fibers and fibril bundles. The original TOC/water slurry and partly fibrillated TOC/water dispersions with low degrees of fibrillation were converted to a sheet and films, respectively, in a short time by membrane filtration, and they had low bulk densities and high porosities. Membrane filtration of an almost completely nanofibrillated TOC/water or TOCN dispersion took a long time, but the as-prepared TOCN films had the highest light transparency, tensile strength, Young’s modulus, and work of fracture. The oxygen permeabilities of the films at 23°C and 50% relative humidity were as low as 1‒2 mL µm m‒2 day‒1 kPa‒1 among the films prepared from the fibrillated TOC/water dispersions with wide turbidity range of 0.01‒ 0.45. Therefore, TEMPO-oxidized CNNeW films with the versatile optical, porous, and mechanical properties but similarly low oxygen permeabilities can be prepared by controlling the degree of fibrillation of the TOC/water slurry.